Intra-Year Trends in the Degree of Association between Accounting Numbers and Security Prices - Tse, Senyo (The Accounting Review, 1986)
[This study uses two representative cross-sectional valuation models to examine trends in the explanatory power of given sets of financial data for security prices. The primary objective is to examine joint hypotheses on the validity of valuation models and the manner in which financial statement data are assimilated into the information set reflected in prices, and subsequently replaced by other data. The observed trends support the informativeness trend hypotheses, suggesting that the valuation models studied capture important elements of the security pricing relationship. An examination of intra-year movements showed substantial variation around the trends, suggesting the presence of temporary influences on model explanatory power. Possible explanations for these phenomena are offered.]